miR-29c-3p inhibits autophagy and cisplatin resistance in ovarian cancer by regulating FOXP1/ATG14 pathway - Hu, Zhenhua; Cai, Mingbo; Zhang, Ying; Tao, Lingling; Guo, Ruixia (Cell cycle (Georgetown, Tex.), 2020)
Autophagy, characterized by the elevator of autophagy-related gene 14 (ATG14) and the dysregulation of autophagy-related proteins, contributes to the cisplatin (DDP) resistance in ovarian cancer. Forkhead box protein P1 (FOXP1), which is a well-defined transcription factor, is reported to have the oncogenic effect on ovarian cancer. This study aims to identify the effect of miR-29c-3p/FOXP1/ATG14 pathway in regulating autophagy and DDP resistance in ovarian cancer. The expressions of miR-29c-3p, FOXP1, ATG14 and autophagy-related proteins were detected in DDP-sensitive ovarian cancer cell lines (SKOV3 and A2780) and DDP-resistant cell lines (SKOV3/DDP and A2780/DDP). Cell viability was detected using the MTT assay. The therapeutic effect of miR-29c-3p overexpression was observed in the xenograft model of nude mice.Compared with DDP-sensitive cells, miR-29c-3p was decreased in DDP-resistant cells, and an enhancement of FOXP1, ATG14, autophagy, and drug resistance was shown in DDP-resistant cells. The anti-resistant effect of miR-29c-3p was observed as overexpressing miR-29c-3p inhibited cell viability of DDP-resistant cells. Moreover, FOXP1 was a target of miR-29c-3p, which was confirmed by the luciferase reporter assay, and ATG14 was transactivated by FOXP1, which was confirmed by the ChIP assay. Overexpression of miR-29c-3p increased DDP sensitivity by downregulating FOXP1/ATG14 in vitro. The tumor volume was reduced after the injection of miR-29c-3p-overexpressing SKOV3/DDP cells in vivo. Overexpression of miR-29c-3p inhibited autophagy and DDP resistance partly via downregulating FOXP1/ATG14 pathway, suggesting miR-29c-3p as a novel target in overcoming DDP resistance in ovarian cancer.